Pulmonary embolism: CT signs and cardiac biomarkers for predicting right ventricular dysfunction - Henzler, Thomas; Röger, Susanne; Meyer, Mathias; Haghi, Dariusch; Kaminski, Wolfgang E.; Neumaier, Michael; Schönberg, Stefan; Fink, Christian (The European respiratory journal, 2012)
The aim of this study was to prospectively evaluate the accuracy of quantitative cardiac computed tomography (CT) parameters and two cardiac biomarkers (N-terminal-pro-brain natriuretic peptide (NT-pro-BNP) and troponin I), alone and in combination, for predicting right ventricular dysfunction (RVD) in patients with acute pulmonary embolism. 557 consecutive patients with suspected pulmonary embolism underwent pulmonary CT angiography. Patients with pulmonary embolism also underwent echocardiography and NT-pro-BNP/troponin I serum level measurements. Three different CT measurements were obtained (right ventricular (RV)/left ventricular (LV) axial, RV/LV 4-CH and RV/LV volume). CT measurements and NT-pro-BNP/troponin I serum levels were correlated with RVD at echocardiography. 77 patients with RVD showed significantly higher RV/LV ratios and NT-pro-BNP/troponin I levels compared to those without RVD (RV/LV axial 1.68±0.84 versus 1.00±0.21; RV/LV 4-CH 1.52±0.45 versus 1.01±0.21; RV/LV volume 1.97±0.53 versus 1.07±0.52; serum NT-pro-BNP 6,372±2,319 versus 1,032±1,559 ng·L −1; troponin I 0.18±0.41 versus 0.06±0.18 g·L−1). The area under the curve for the detection of RVD of RV/LV axial, RV/LV 4-CH, RV/LV volume, NT-pro-BNP and troponin I were 0.84, 0.87, 0.93, 0.83 and 0.70 respectively. The combination of biomarkers and RV/LV volume increased the AUC to 0.95 (RV/LV volume with NT-pro-BNP) and 0.93 (RV/LV volume with troponin I). RV/LV volume is the most accurate CT parameter for identifying patients with RVD. A combination of RV/LV volume with NT-pro-BNP or troponin I measurements improves the diagnostic accuracy of either test alone.
Gesehen am 09.05.2018